Optical spin-orbit torque in heavy metal-ferromagnet heterostructures - Gyung-Min Choi (Nature Portfolio, 2020)
It is known that torques can be exerted on spins in a ferromagnet (FM) layer when an in-plane electric current is injected into a heavy metal (HM) layer in contact with the FM layer. Here, the authors demonstrate that torques can be generated without the current injection by shining instead circularly polarized light on the HM.